Evaluación del programa de seguridad del paciente en la Unidad Especial de Salud de la Universidad de Córdoba (2023)
Patient safety is essential to guarantee the quality of processes and improve care in all Health Institutions. The objective of this work is to evaluate compliance with the patient safety program at the health unit of the University of Córdoba so that said program is carried out in accordance with current regulations Patient safety is a component of health care that has been gaining strength in recent decades, and it should be noted that the special health unit has realized that preventing possible adverse events in care, acting on time, correcting mistakes and learn from them, it is important to create a climate of safety that leads to the Continuous Improvement of Quality in Health care. Evaluating the Patient Safety program should be our maximum, specific aspiration; Starting with the senior management of the institution, a culture oriented towards quality and safety is characterized by a strong and supportive alliance, where the probabilities of risks of adverse events are neutralized, whose program integrates policies and processes related to quality, talent human, physical and technological resources and information systems for reporting adverse events and incidents, assuming challenges and responsibilities to achieve the objectives.